The role of Information technology in conducting production planning and control: a case study - Martins, Carlos Fernando; Prada, Charles Anderson; Abreu, Aline França de; Queiroz, Abelardo Alves de (Revista Gestão da Produção Operações e Sistemas, 2008)
This article presents the results of an exploratory research conducted in a lager manufacturing company inorder to understand the influences of the Information Technology (IT) in the activities of production planningand control. The research shows that with the development of information systems from isolated systems to integratedsystems, activities related to production planning, programming and control were also influenced by newcomputer applications to integrate the information industry and to search for better operational efficiency. Fourmain results were obtained: i) the IT improves the efficiency of operations production planning, scheduling andcontrol through corporate information systems, ii) the IT improves the industrial information communication,helping to integrate computer from the collection of data up to the plans of production; iii) the IT facilitates themanagerial decision-making to estimates the market and risks; iv) and IT supports innovation in the developmentof new products and services.Keywords: Industrial Information System; Information Technology; Integrated Manufacturing System; ProductionPlanning and Control; MRP.